2005
DOI: 10.1074/jbc.m503730200
|View full text |Cite
|
Sign up to set email alerts
|

Direct DNA Binding Activity of the Fanconi Anemia D2 Protein

Abstract: It is known that the Fanconi anemia D2 protein is vital for protecting the genome from DNA damage, but what activities this protein has are unknown. In these experiments we purified full-length Fanconi anemia protein D2 (FANCD2), and we found that FANCD2 bound to DNA with specificity for certain structures: double strand DNA ends and Holliday junctions. Proteins containing patient-derived mutations or artificial variants of the FANCD2 protein were similarly expressed and purified, and each variant bound to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 39 publications
1
60
2
Order By: Relevance
“…However, it was clear that monoubiquitin- ated FANCD2 did strongly associate with chromatin. Biochemical studies suggest that FANCD2 is able to bind directly to DNA (30). In addition, this protein is phosphorylated by both ATR and ATM DNA checkpoint kinases, which are induced by different kinds of DNA lesions (1,37).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was clear that monoubiquitin- ated FANCD2 did strongly associate with chromatin. Biochemical studies suggest that FANCD2 is able to bind directly to DNA (30). In addition, this protein is phosphorylated by both ATR and ATM DNA checkpoint kinases, which are induced by different kinds of DNA lesions (1,37).…”
Section: Discussionmentioning
confidence: 99%
“…Using FANCD2 purified from baculovirus-infected SF9 insect cells, the Parvin group originally determined that full-length FANCD2 binds to dsDNA and Holliday junctions (HJs), quadruplex heteroduplex DNA intermediates that arise during HR. 163 Similarly, the Zhang group purified full-length FANCI and demonstrated that it can bind to multiple DNA substrates, including HJs, dsDNA, ssDNA, and flap structures, without any apparent structural preference. 31 Longerich et al also demonstrated that purified FANCI is capable of binding to dsDNA, ssDNA, and HJs.…”
Section: Fancd2 and Fanci: Dna Bindingmentioning
confidence: 99%
“…FANCJ/BRIP1, which is thought to play a role downstream in the FA pathway (23,24,39), is a 5Ј-to-3Ј DNA helicase with substrate specificity towards splayed DNA duplexes (Y-shaped DNA) (14). In support of a role for FA proteins in the processing of DNA structures, a recent study demonstrated that recombinant FANCD2 has direct DNA binding activity in vitro (38). Moreover, Ciccia et al reported that recombinant FANCM is directed to branched DNA structures by a novel FA core complex member, FAAP24 (4).…”
mentioning
confidence: 99%